2018
DOI: 10.1186/s12913-018-3321-5
|View full text |Cite
|
Sign up to set email alerts
|

An integrated oral health program for rural residential aged care facilities: a mixed methods comparative study

Abstract: BackgroundPeople in residential aged care facilities (RACF) are at very high risk of developing complex oral diseases and dental problems. A multidisciplinary approach incorporating oral health professionals and RACF staff is important for improving and sustaining oral health in RACFs. However, difficulties exist with access to oral health services for RACFs, particularly those in regional and rural areas. This study investigated the impact and experience of an integrated oral health program utilising tele-den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 54 publications
2
70
0
1
Order By: Relevance
“…Two studies investigated the feasibility and the accuracy of Teledentistry for diagnosis dental pathology using the traditional face-to-face examination as gold standard [23,24]. Four papers were aimed at assessing patients and health practitioners experiences about Teledentistry by the use of questionnaires [23], direct observation of nurses [25], surveys and clinical audit charts [26,27]. Finally, three studies reported also a cost analysis and a cost description of Teledentistry in residential aged care facilities [23,26,28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies investigated the feasibility and the accuracy of Teledentistry for diagnosis dental pathology using the traditional face-to-face examination as gold standard [23,24]. Four papers were aimed at assessing patients and health practitioners experiences about Teledentistry by the use of questionnaires [23], direct observation of nurses [25], surveys and clinical audit charts [26,27]. Finally, three studies reported also a cost analysis and a cost description of Teledentistry in residential aged care facilities [23,26,28].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a previous study stated that Teledentistry has the capacity to reduce appointment waiting lists, triaging and prioritizing appointments, and to provide a rationalization of time, travel and costs for all parties [42]. Additionally, teleconsultation could reduce all the stress generated by travelling to a dental office from home or the residential aged care facility of the patients, especially in those with dementia that could lead to a complete lack of collaboration with dental practitioners [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teledentistry dapat diterima cukup baik di antara para pemberi layanan kesehatan dan pasien dengan meningkatnya efisiensi waktu, efisiensi perjalanan, dan juga biaya [9] . Dalam penelitian lain juga disebutkan bahwa teledentistry juga meningkatkan akses terhadap layanan kesehatan bagi lansia dan penyandang disabilitas [10] .…”
Section: A Studi Literaturunclassified
“…22,23 Across Eastern Australia, initiatives in teledentistry are in use in NSW, Victoria and Queensland. 24 The Victorian Department of Health and Human Services funded DHSV in January 2015 to launch a telehealth programme. The aim of the programme was for teledentistry to enable patients to receive specialist advice and/or advanced care through a clinical alliance between dentists at DHSV funded community dental clinics and RDHM specialist staff.…”
Section: Victoria and Teledentistrymentioning
confidence: 99%